Linking High Involvement Human Resource Practices to Innovative Work Behaviour : The Mediating Effect of Malaysia Financial Sector Employees Work Engagement - Yerembessova, Veronika (2015)
Fostering innovative work behaviour amongst employees has evolved as an important tool for organisations’ survival since it aids the consistent need for improvement and value creation amidst increasing competition. In an effort to understand how such behaviour comes about, this study sets out to examine high-involvement human resource practices as an antecedent to the innovative work behaviour of financial industry employees and whether work engagement mediates this relationship. Based on a sample of 218 financial industry employees working in Malaysia, results showed that recognition, as a dimension of high-involvement human resource practices, was positively related to innovative work behaviour. Furthermore, the relationship between competence development and innovative work behaviour is partially mediated by work engagement. The findings from this study provide essential direction to future research efforts investigating the effects of high-involvement human resource practices and work engagement on the innovative work behaviour of employees in established organisations.